Peranan Penyuluh Pertanian Lapangan Dalam Pembuatan Pupuk Organik Padat (Kasus pada Kelompok Ternak Putra Kertha Santhi, Lingkungan Kebon, Kelurahan Baler Bale Agung, Kecamatan Negara, Kabupaten Jembrana) - SMARA, NI KOMANG MAYA GITA; SUARDI, I DEWA PUTU OKA; AGUNG, I DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol 6 No 1 (2017), 2017)
Role of Field Agricultural Extension Officer in Solid Organic FertilizerProduction, (In the case of Putra Kertha Santhi Group, Kebon – BalerBale Agung Village, Negara District Jembrana Regency) An agricultural extension officer is the agent of change in farmer’s behaviors. Hedoes this by encouraging farmers to change their behaviors to be farmers with betterskills and farmers who be able to make their own decisions, which in turn will leadthem into achieving a better life. The importance of the role of facilitator (FieldAgricultural Extension Officer) and the importance of innovation delivered by him,facilitator should be able to become a leader who can develop and improve theability of farmers in a joint effort to change their lives for the better. This studyaimed to identify the role of field extension officer in solid organic fertilizerproduction either as a communicator, counselor, facilitator, organizer or motivator.This study took place in Putra Kertha Santhi Group. The research sites were selectedby using purposively sampling. The respondents were chosen by using censusmethod in accordance with the number of farmer group members which is 20 people.Method used in this study was descriptive qualitative analysis, which is a researchaiming to provide an overview and explanation of the variables examined. The resultshowed that the role of field agricultural extension officer in the manufacture of solidorganic fertilizer in Putra Kertha Santhi Group is good with the score of 83.4%. Thismeans that the extension officer on duty in Baler Bale Agung Village has been ableto carry out his role as a communicator, counselor, facilitator, organizer andmotivator.
Keywords: role; organic; fertilizer; farmer